Audit of Certification System Governance Using COBIT 5 - Ni Luh Adriani; I Made Surya Sukma Mahardika; Ni Wayan Sri Aryani (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Efficient and effective IT resource management is needed to create solutions and minimize the risk of implementing Information Technology (IT) in organizations. The COBIT 5 framework helps in the information technology audit process because it covers all elements of the information technology used. Training Institute X is an institution to obtain certification from Tourism courses/training. Currently Training Institute X is developing information technology utilization in improving the quality of business processes in IT systems according to the vision, mission and purposes of the Training Institute X set. The need for an audit is because in its implementation there is still the use of information technology that has not been properly managed and alignment in the information technology process and business processes that have not yet been evaluated. In this paper the method to be used is COBIT 5 by using 3 domains that have been mapped according to the company's objectives, namely EDM, DSS and APO. Capability level measurement results in each domain of IT governance audit use COBIT 5 on the EDM and APO domains on level 2 (Managed process) and DSS on level 1 (Performed process).